Probation Officers' Attitudes on Illinois Electronic Monitoring Program for Drug Offenders - Jones-Dilworth, Erika J (2018)
Probation Officers' Attitudes on Illinois Electronic Monitoring Program For Drug Offenders by Erika Jones-Dilworth MPA, Governors State University, 2009 BS, Governors State University, 2007 Dissertation Submitted in Partial Fulfillment of the Requirements for the Degree of Doctor of Philosophy Public Policy & Administration Walden University November 201